2013
DOI: 10.1590/jvb.2013.035
|View full text |Cite
|
Sign up to set email alerts
|

Relacao entre o nivel de atividade fisica estimado pelo Baltimore Activity Scale for Intermittent Claudication e a pedometria em pacientes com claudicacao intermitente

Abstract: Background: The levels of physical activity of patients with intermittent claudication (IC) are usually reduced. The Baltimore Activity Scale for Intermittent Claudication (BASIC) was designed to measure physical activity levels of patients with IC, but its validation was conducted against only two days of monitoring with an accelerometer, and it remains unclear whether BASIC provides information about weekly physical activity levels. Objective: To analyze the correlation between physical activity levels of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Although there are similar findings in the literature (5,22) , the results of the present study need to be interpreted with caution. The reliability of the BASIC in our sample did not obtain an acceptable level (<0.70).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Although there are similar findings in the literature (5,22) , the results of the present study need to be interpreted with caution. The reliability of the BASIC in our sample did not obtain an acceptable level (<0.70).…”
Section: Discussionsupporting
confidence: 73%
“…Studies support these findings in patients with IC (22) . A study with 150 patients with IC, aged between 30 and 80 years, quantified the level of physical activity using the BASIC in these patients and found that the mean BASIC score was 4.2 (1.9) (22) . The mean BASIC score showed a statistically significant association with the total MIF scores.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation